Spatial and timeframe distribution of diverse pedestrian activities in the street network of southeast asian developing cities - Shino Miura; Munehito Yoshida; Fumihiko Nakamura; Pattamaporn Wongwiriya; Shinji Tanaka; Ryo Ariyoshi (Journal of Asian Architecture and Building Engineering, 2024)
This research clarifies the spatial and timeframe distribution of pedestrian activities with the demand for “place function” in the street network of central business district areas of two Southeast Asian developing cities, Da Nang in Vietnam and Khon Kaen in Thailand. The research acquired data on pedestrian activities by observation in three timeframes and visualization to clarify the features of street segments. Notably, the segments with the highest activity demand were compared with their integration value in space syntax theory and adjacent ground floor uses. The findings indicate that the volume of optional activities is higher than other activities and increases at night. The segment with the highest activity density and integration value was a sufficient condition for the high ratio of commercial ground floor use in the target cities. Moreover, the research noted the uniqueness of each city. Da Nang is relatively dispersed due to the existence of open spaces, including a river, inducing optional and social activities, but Khon Kaen is concentrated along the main street. As insights, a city should create a management strategy for places of a broader area of the CBD, not only in the centre’s main street.